Generation XYZ’s Perception on Zakat Mal and Tax: The Planned Behavior Perspective - Arfah Habib Saragih (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
The research aims to apply the theory of planned behavior to predict respondents’ intention of offering zakat mal (wealth) and tax payment. The research brings questionnaires, aiming to generate a descriptive research. Technique of analysis being applied is the Partial Least Square (PLS) with SmartPLS software. The descriptive statistics shows that respondents have deep understanding between zakat mal and tax. In addition, the analysis using PLS reveals that attitude, subjective norm, and behavioral control influence one’s intention to pay zakat mal and tax, while behavioral intention affects actual behavior in paying the two. Keywords: zakat mal, tax, planned behavior